Molecular epidemiology of methicillin-susceptible Staphylococcus aureus (MSSA) isolated from milk of cows with subclinical mastitis - Bonsaglia, E. C.R. [UNESP]; Silva, N. C.C.; Rossi, B. F. [UNESP]; Camargo, C. H.; Dantas, S. T.A. [UNESP]; Langoni, H. [UNESP]; Guimarães, F. F. [UNESP]; Lima, F. S.; Fitzgerald, J. R.; Fernandes, A. [UNESP]; Rall, V. L.M. [UNESP] (Elsevier, 2018)
Bovine mastitis has been a concern for dairy herd for decades. The adaptation capacity of one of the main species responsible for this disease, Staphylococcus aureus (S. aureus), plays a pivotal role in this issue. The aim of this study was to establish a molecular and phenotypic profile of 285 S. aureus strains isolated from milk of subclinical mastitis cows from 18 different farms in São Paulo State using spa typing, multilocus sequence typing (MLST), pulsed field gel electrophoresis (PFGE), agr cluster (I, II, III and IV) typing, PCR for genes including enterotoxins (sea, seb, sec, sed, see, seg, seh, sei), toxic shock syndrome toxin (tsst-1), and Panton-Valentine leucocidin (pvl), as well as in vitro resistance assays for 12 antibiotics. The results showed a wide variety of strains with a high toxigenic potential; concomitantly, sec, seg and seh were prevalent. In addition, we observed a predominance of the spa types t605 (ST 126, CC126) and t127 (ST1, CC1) and the unusual presence of t321 causing bovine mastitis, which has been previously reported only in swine. The most frequent ST were ST126 (70.5%) and ST1 (10.5%). Regarding PFGE, we observed four major groups and six profile patterns. The highest resistance was observed for streptomycin (9.5%), followed by tetracycline (3.5%), clindamycin (9.3%), and erythromycin (2.8%). The tsst-1 gene was detected in 36.8% of isolates and pvl was not observed. One hundred and thirty-six (47.7%) isolates possessed agr type II, followed by types III (20%) and I (8.1%), with type IV not being detected. We observed that the same spa type could result in different PFGE profiles, so the exclusive use of spa type sequences can lead to incorrect interpretations regarding the spread of clones in an epidemiological context.